Cavernous lymphangioma of the spleen in children: about a case - Torres, David Héctor; Lattaro, Diver (Cirugía del Uruguay, 1972)
A case of Vavernous Limphangiome of the spleen in a 13 years old boy is recorded. It was discovered in an operation due to hydatic cyst of the liver. References are reviewed, recognising its place in the classification of splenic cysts and remembering its etiology, pathology anatomy and clinical features.